External rectal prolapse: abdominal or perineal repair for men? A retrospective cohort study. (21st February 2022) - Hu, Bang; Zou, Qi; Xian, Zhenyu; Su, Dan; Liu, Chao; Lu, Li; Luo, Minyi; Chen, Zixu; Cai, Keyu; Gao, Han; Peng, Hui; Cao, Wuteng; et al.
Abstract: Background: External rectal prolapse is a relatively rare disease, in which male patients account for a minority. The selection of abdominal repair or perineal repair for male patients has rarely been investigated. Methods: Fifty-one male patients receiving abdominal repair (laparoscopic ventral rectopexy) or perineal repair (Delorme or Altemeier procedures) at the Sixth Affiliated Hospital of Sun Yat-sen University (Guangzhou, China) between March 2013 and September 2019 were retrospectively analysed. We compared the recurrence, complication rate, post-operative defecation disorder, length of stay, and quality of life between the abdominal and perineal groups. Results: Of the 51 patients, 45 had a complete follow-up, with a median of 48.5 months (range, 22.8–101.8 months). A total of 35 patients were under age 40 years. The complication rate associated with abdominal repair was less than that associated with perineal repair (0% vs 20.7%, P = 0.031) and the recurrence rate was also lower (9.5% vs 41.7%, P = 0.018). Multivariate analysis showed that perineal repair (odds ratio, 9.827; 95% confidence interval, 1.296–74.50; P = 0.027) might be a risk factor for recurrence. Moreover, only perineal repair significantly improved post-operative constipation status (preoperative vs post-operative, 72.4% vs 25.0%, P = 0.001). There was no reported mortality in either of the groups. No patient's sexual function was affected by the surgery. Conclusions: Both surgical approaches were safe in men. Compared with perineal repair, the complication rate and recurrence rate for abdominal repair were lower. However, perineal repair was better able to correct constipation.